Spring in the air with ‘Sakura’ in UMP - Siti Nur Azwin, Zulkapri (2021)
PEKAN, 30 March 2021 - The phenomenon of Tecoma flowers, or fashionably referred to by locals as ‘sakura’, is once again beautifying Malaysia’s scenery.